2018
DOI: 10.3390/ijms19072066
|View full text |Cite
|
Sign up to set email alerts
|

Role of Arginine 117 in Substrate Recognition by Human Cytochrome P450 2J2

Abstract: The influence of Arginine 117 of human cytochrome P450 2J2 in the recognition of ebastine and a series of terfenadone derivatives was studied by site-directed mutagenesis. R117K, R117E, and R117L mutants were produced, and the behavior of these mutants in the hydroxylation of ebastine and terfenadone derivatives was compared to that of wild-type CYP2J2. The data clearly showed the importance of the formation of a hydrogen bond between R117 and the keto group of these substrates. The data were interpreted on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…From our simulations, it was found that these three probes were capable of binding to the catalytic site of CYP2J2, especially for M2 and M3 even when their initial binding poses deviated from the final active conformers, indicating a high binding preference of M2 and M3 to CYP2J2. The distance from the heme iron to the metabolic site of the substrate was assumed to be related to the rate of metabolism of CYP2J2 12,31 . Based on this assumption, M1 (3.7 ± 0.2 Å) should exhibit a higher reactivity than M3 (4.3 ± 0.1 Å), which seemed to contradict the experimental results.…”
Section: Structural Basis For the High Binding Affinity Of M2 To Cyp2j2mentioning
confidence: 99%
See 1 more Smart Citation
“…From our simulations, it was found that these three probes were capable of binding to the catalytic site of CYP2J2, especially for M2 and M3 even when their initial binding poses deviated from the final active conformers, indicating a high binding preference of M2 and M3 to CYP2J2. The distance from the heme iron to the metabolic site of the substrate was assumed to be related to the rate of metabolism of CYP2J2 12,31 . Based on this assumption, M1 (3.7 ± 0.2 Å) should exhibit a higher reactivity than M3 (4.3 ± 0.1 Å), which seemed to contradict the experimental results.…”
Section: Structural Basis For the High Binding Affinity Of M2 To Cyp2j2mentioning
confidence: 99%
“…For the terfenadone derivatives M10 and M12 in Fig. 1, CYP2J2 exhibited regioselectivity of hydroxylation of the Cβ atom, and Arg117 was assumed to play a critical role 12,31 . Based on the homology model of CYP2J2, a narrow channel of access to the heme was identified, which included Ile127, Phe310, Ile376, and Val380 12 .…”
Section: M1-m3mentioning
confidence: 99%
“…In previous work, our groups investigated the interaction of AA with human CYP2J2 and revealed Arg117 as a key player in the recognition of this substrate [3], although these simulations were relatively short (50 ns). Simulations from other studies have come to diverse conclusions about the role of individual residues in the active site [46]. Here, we tried to investigate further using much more extensive simulations of both wild type and mutant forms of the enzyme.…”
Section: Objectivementioning
confidence: 99%